MEMBACA ULANG TEKS AL-QURAN DALAM PERSPEKTIF FEMINISME SERTA PENGARUHNYA TERHADAP AKSES KEADILAN SOSIAL DI INDONESIA - dian andrisari (Jurisprudensi : Jurnal Ilmu Syariah, Perundangan-Undangan dan Ekonomi Islam, 2019)
This article examines the influence of feminist discourse through the contextual approach of the holy book (Qur'an) and its influence on access to social justice. The main argument of this article states the contextualization of feminist discourse in Islam by re-reading the verses of the Qur’an which leds misogynistic in practice experiencing complexity and difficult paths. Using a feminine perspective, this article traces the interpretation of the Qur'anic text and the hadiths are detrimental to women. Therefore, "locality" is a consideration because women cannot be seen as one or monolithic. For this reason, a "locality" methodology meeting is needed in seeing the struggle of feminism in revising the authority of interpretation in an effort to make feminist studies a policy study, especially for and for the empowerment of marginal people in various parts of the world.